Maintaining dendritic cell viability in culture. Issue 2 (February 2015) - Vremec, David; Hansen, Jacinta; Strasser, Andreas; Acha-Orbea, Hans; Zhan, Yifan; O'Keeffe, Meredith; Shortman, Ken
Highlights Mouse DCs die even more rapidly in culture than in vivo. GM-CSF conserves the culture viability of conventional DCs, but not of plasmacytoid DC. Plasmacytoid DCs from mice overexpressing Bcl-2 have prolonged survival in culture.